Dynamic performance evaluation of ultrasonic composite horn for machining soft and brittle composites - Muhammad Asif Mahmood Qureshi,; Nasir Hayat,; Zia ul Rehman Tahir,; Khurram Hameed Mughal,; Fazal Ahmad Khalid,; Asif Ali Qaiser,; Zhang, Jianfu (Penerbit Universiti Kebangsaan Malaysia, 2023)
Ultrasonic horn (USH) is a key component in high intensity power ultrasonic systems to enhance vibration amplitude at tool end (VATE). Due to high intensity ultrasonic operating frequency of at least , horn may be exposed to high stress levels leading to failure. The primary objective of USH design is to achieve high vibration amplification with good strength. In present research, the effect of fillet radius / roundness on ultrasonic composite horn (USCH) performance was investigated for various materials: stainless steel, aluminum, titanium, and steel, respectively, using finite element analysis (FEA). USCH was developed for ultrasonic machining of soft and brittle composites, especially Nomex honeycomb composite. The important performance parameters considered were longitudinal modal frequency (LMF), Von Mises (VM) stresses, magnification factor (MF), VATE and factor of safety (FS). LMF was found to increase, with decrease in VATE and VM stresses by increasing the roundness at the transition section. Titanium was observed to be highly appropriate material for USCH, because it delivered at least 81.6 % to 142.62 % more vibration amplification and up to 4 times higher factor of safety, consequently, operating life in comparison to other USCH materials.